The design and development of a hybrid off-job crafting intervention to enhance needs satisfaction, well-being and performance: a study protocol for a randomized controlled trial - Merly K. Kosenkranius; Floor A. Rink; Jessica de Bloom; Machteld van den Heuvel (BMC, 2020)
Abstract Background Employees dealing with job demands such as high workload and permeable work-life boundaries could benefit from bottom-up well-being strategies such as off-job crafting. We have developed a hybrid off-job crafting intervention to promote off-job crafting, a proactive pursuit to adjust one's off-job time activities to satisfy one's psychological needs. This hybrid intervention contains both on-site (two trainings) and online elements (smartphone app) to enhance employees' well-being and performance within different life domains. Methods The study is designed as a randomized controlled trial with an intervention group and a waitlist control group. The study population will be Finnish knowledge workers. The intervention program focuses on six psychological needs (detachment, relaxation, autonomy, mastery, meaning, and affiliation) proposed by the DRAMMA model. The intervention will consist of the following components: 1) an on-site off-job crafting training, 2) an individual off-job crafting plan for the four-week intervention period, 3) Everydaily smartphone app usage, and 4) a training session for reflection. The study outcomes are assessed with online questionnaires once at baseline, weekly during the intervention period and twice after the intervention (two-week and six-week follow-up). Moreover, during the second training session, participants will participate in a process evaluation to shed light on the mechanisms that can affect the effectiveness of the intervention. Discussion We expect that the intervention will stimulate off-job crafting behaviors, which may in turn increase well-being and performance in both non-work and work domains during and after the intervention (compared to baseline and to the control group). The intervention may provide employees with additional resources to deal with various stressors in life. Furthermore, this off-job crafting intervention could also offer performance benefits for the employers such as increased organizational citizenship behaviors among employees. Trial registration The Netherlands Trial Register (NTR): NL8219, December 9, 2019. Registered retrospectively. https://www.trialregister.nl/trial/8219